2016
DOI: 10.1177/2319510x16650058
|View full text |Cite
|
Sign up to set email alerts
|

Emotionality Does but Spirituality Does Not: The Effect of Emotional and Spiritual Intelligence on Organisational Citizenship Behaviour

Abstract: The current study explores the relationship between emotional intelligence (EI) and spiritual intelligence (SI) and the consequent effect of both on organisational citizenship behaviour (OCB). The piece of writing measures the concept of EI, SI and OCB across 555 respondents from various public and private sector organisations in India. The goodness of fit is measured with the help of AMOS by using structural equation modelling (SEM), and association between the variables is examined by using path analysis for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…This research uses emotional intelligence, servant leadership and organizational commitment variables. Some of the researchers studied those variables were Indriani and Sari [6], Ibrahim [7], Yadaf and Punia [8], exemplified that emotional intelligence had positive and significant effect on OCB. Mira and Margareta [9], Sedarmayanti and Kuswanto [10], Al-amri, et.al.…”
Section: A Background Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This research uses emotional intelligence, servant leadership and organizational commitment variables. Some of the researchers studied those variables were Indriani and Sari [6], Ibrahim [7], Yadaf and Punia [8], exemplified that emotional intelligence had positive and significant effect on OCB. Mira and Margareta [9], Sedarmayanti and Kuswanto [10], Al-amri, et.al.…”
Section: A Background Of the Studymentioning
confidence: 99%
“…The research has been conducted by Indriani and Sari [6], Yadav and Punia [8] and Naderi Anari [20], found out that emotional intelligence had positive and significant effect on OCB.…”
Section: G Hypothesis Development 1) the Relationship Of Emotional Imentioning
confidence: 99%
“…However, not all studies of spiritual intelligence with OCB produce the same findings. Like research by Yadav and Punia (2016) found that spiritual intelligence unsignificant effect on OCB. The difference between the findings of the researchers made spiritual intelligence in relation to OCB interesting to be examined until now.…”
Section: Introductionmentioning
confidence: 62%
“…Higher scores indicated better conditions. Reliability of the third tool, based on Cronbach's alpha, was reported as 0.89 (16). Questionnaires were completed as self-reported and semisupervision form.…”
Section: Methodsmentioning
confidence: 99%
“…Organizational behavior has been linked to overall organizational effectiveness, thus, these types of employee behaviors have important consequences in the workplace (15). In addition, the OCB is useful in the prediction of organizational virtuousness as well as job performance (16).…”
Section: Introductionmentioning
confidence: 99%